Meningkatkan Minat Literasi Membaca Siswa Sekolah Dasar - Jeni Padila Nopita Sari Jeni; Celika Zenti; Elyusra Elyusra; Mahdijaya Mahdijaya (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The purpose of implementing the Teaching Campus program is to empower students to assist the teaching process in elementary and junior high schools around the village/city where they live. The method in this service is a survey research method. The steps of situation analysis and program planning as well as the results obtained in the implementation of the Teaching Campus program succeeded in increasing the reading interest of students in SD Negeri 204 North Bengkulu Regency. The problem encountered is that there are students who are not interested in participating in this literacy activity, this literacy activity plan will be carried out after class hours are over and take place in the classroom. Efforts were made before carrying out this literacy activity, namely, we Campus Teaching students discussed it with the principal, teachers, and students, after discussing the program that we would run during the Teaching Campus program we got a good response from the school and students. After this literacy activity was carried out, the results obtained were quite good, students became more active in reading, students were more active in responding to each lesson in the form of discussions or groups.